Autorzy:Alina Przychoda, Zygmunt Łaszczyk
Wydawnictwo:WSiP
Rok wydania:2015
Oblicz wartość wyrażenia dla x=-3/44.67 gwiazdek na podstawie 6 opinii

Oblicz wartość wyrażenia dla x=-3/4

5Zadanie
6Zadanie
7Zadanie
8Zadanie

a)

`(2x^2-4y)/(15xy)=(2*(-3/4)^2-4*(1/3))/(15*(-(strike3)/4)*1/(strike3))=(strike2*9/(strike16)-4/3)/(15*(-1/4)*1/1)=(9/8-4/3)/(-15/4)= (27/24-32/24)/(-15/4)= (-5/24)/(-15/4)=(strike5)/(strike24)*(strike4)/(strike15)= 1/6*1/3= 1/18` 

b)

`(15xy-2x^2)/(3y^2)= (15*(-3/4)*1/3-2*(-3/4)^2)/(3*(1/3)^2)=(-(strike45)/4*1/(strike3)-strike2*9/(strike16))/((strike3)*1/(strike9))= (-15/4*1/1-9/8)/(1/3)=(-15/4-9/8)/(1/3)=(-30/8-9/8)/(1/3)=-39/8 *3=-117/8` 

c)

`(2x+7y-xy)/(8x^2)=(2*(-3/4)+7*1/3-(-3/4)*1/3)/(8*(-3/4)^2)= ((-6/4)+7/3+(strike3)/4*1/(strike3))/(strike8*9/(strike16))=(-18/12+28/12+1/4)/(9/2)=(10/12+3/12)/(9/2)=13/(strike12)*(strike2)/9=13/6*1/9=13/54 `